What is veteran suicide prevention really about? Questions from the community to researchers - Brandy M. Fox (Qualitative Research in Medicine & Healthcare)
Military veterans are one of the most researched groups in healthcare in the United States. This population has extremely high rates of suicide attempts and completions. Despite increasing research focus, millions of dollars in funding, and being designated as a high clinical priority, rates of suicidal behavior continue to rise among veterans. Veterans are extremely concerned about this trend and critical of some suicide prevention projects. This study engaged 20 veterans who are connected to individuals within the military community who have attempted or completed suicide. Through semi-structured interviews, participants expressed a profound sense of disconnection from existing policies, treatments, and strategies aimed at preventing veteran suicide. During the course of the interviews, participants posed their own questions: Why is the public really concerned about veteran suicide? Why won’t the public recognize its part in the veteran suicide epidemic? Why won’t the medical industry listen and collaborate with us? This study underscores the critical need for all stakeholders involved in veteran suicide prevention to reflect on these concerns and to incorporate veterans’ insights into future prevention strategies, creating a more responsive and effective approach.